2003
DOI: 10.1016/s0020-7292(02)00334-x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium–phosphorus–magnesium homeostasis in pregnant women after renal transplantation

Abstract: Women after kidney grafting present vital aberrations in calcium-phosphorus-magnesium homeostasis during pregnancy. The most significant changes are associated with calcium metabolism (high increase in serum Ca levels and impairment of renal elimination of calcium). The observed changes may be influenced by the doses of immunosuppressive agents and disturbed renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Calcium and magnesium have a role in the regulation of myometrial activity and maternal serum levels decrease with advancing gestational weeks (7). In the second trimester, premature uterine contraction in women may be related to the homeostasis of calcium-phosphorusmagnesium (8). Maternal calcium and vitamin 25 (OH) D levels were found to be associated with PC and it was concluded that the placenta is important in vitamin D regulation (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium and magnesium have a role in the regulation of myometrial activity and maternal serum levels decrease with advancing gestational weeks (7). In the second trimester, premature uterine contraction in women may be related to the homeostasis of calcium-phosphorusmagnesium (8). Maternal calcium and vitamin 25 (OH) D levels were found to be associated with PC and it was concluded that the placenta is important in vitamin D regulation (9,10).…”
Section: Introductionmentioning
confidence: 99%